The Effect of Combining Femtosecond Laser and Electron Irradiation on Silica Glass - Nadezhda Shchedrina; Roqya Allaoui; Matilde Sosa; Gergely Nemeth; Ferenc Borondics; Nadege Ollier; Matthieu Lancry (Nanomaterials)
This study investigates the structural and optical responses of silica glass to femtosecond (fs) laser irradiation followed by high-energy electron (2.5 MeV, 4.9 GGy) irradiation. Using optical microscopy and spectroscopy techniques, we analyzed retardance, phase shifts, nanograting periodicity, and Raman D2 band intensity, which is an indicator of local glass densification. S-SNOM and nano-FTIR measurements further revealed changes in the Si–O–Si vibrational bands, indicating partial relaxation of the densified nanolayers under electron irradiation. Our findings reveal significant optical modifications due to subsequent electron irradiation, including reduced retardance and phase values, which are in agreement with the relaxation of the local densification. SEM analysis confirmed the preservation of nanogratings’ morphology including their periodicity. Apart from revealing fundamental aspects related to glass densification within nanogratings, this study also underscores the potential of combined fs-laser and electron irradiation techniques in understanding silica glass behavior under high radiation conditions, which is crucial for applications in harsh environments.